The impact of HIV on fertility aspirations in Uganda. - Snow, Rachel C; Mutumba, Massy; Powers, Gregory; Evans, Lindsey; Rukundo, Edith; Abesiga, Lenard; Kabasindi, Joy; Ford, Tegan; Mugyenyi, Godfrey (Population Study Center, 2011)
This paper reports on a study of whether a women’s personal HIV status, the presence of an HIV+ child in the household, or the presence of foster children in the household, has a measureable impact on a woman’s desire for future offspring, net of parity, or son parity, in an area of Uganda with high fertility norms. A survey of 1,594 women age 18-49 yrs visiting outpatient services at Mbarara Regional Hospital in Mbarara Uganda was conducted from June through August 2010. Among survey participants, 59.7% were HIV-positive (HIV+) and 40.3% were HIV-negative (HIV-); and 96.4% of the HIV+ women were currently on anti-retroviral therapy (ART). Logistic regression models were used to investigate the relationships between fertility desires and HIV status, household, and social factors. We found that, despite high fertility norms in Uganda and almost universal use of ART in our sample, HIV+ women were significantly less likely to desire future childbearing relative to HIV- women, and pregnant HIV+ women reported their pregnancies were a problem. The findings suggest a potential unmet need for family planning among HIV+ women in Uganda.
Keywords: HIV; Fertility Aspirations; Uganda